METODE PEMBELAJARAN SAINS ANAK USIA 5-6 TAHUN DI PAUD LABORATORIUM MODEL UNIVERSITAS MUHAMMADIYAH PONTIANAK - Wahyuda Dwi Handoko; Marmawi Marmawi; Fadillah Fadillah (Universitas Tanjungpura, 2019)
Abstract Science learning in early childhood has a very important role in helping lay the foundation of the ability and formation of the expected human resources. Awareness of the importance of learning science in children will be even higher when realizing that we live in a dynamic, evolving and changing world that is even more and more toward the future, increasingly requires science. Science development in Kindergarten will be carried out well when using the right method. The general objective in this study was to determine the Application of Science Learning Methods in Children Aged 5-6 years in PAUD Laboratory Model Muhammadiyah University of Pontianak. The conclusion of this study is that the teacher does not apply only one method of learning when conducting activities but the teacher combines several learning methods that are in accordance with the material to be delivered. Teachers are expected to pay attention to the method used and the steps in using the learning method so that the learning objectives are well implemented. Keywords: Early Childhood, Learning Methods, Science